The objective is not the goal; it is not the end; it is not the object nor the result to be achieved - Bermúdez Sarguera, Rogelio; Pentón Quintero , Aylin (Revista Minerva, 2023)
In this article, the problem that concerns the objectives is addressed, a concept that, although hackneyed by research in the fields of psychology, pedagogy and mainly by didactics, still rests in the pipeline of research, waiting of the methodological analysis that pulsates its multiple edges, given its elevation to category level. Thus, the general objective of this work is to assess the taxonomic position of this concept that denies, in the dialectical sense, the former taxonomy of objectives, current in the educational field and that defends, without any theoretical-methodological foundation, the attempts to structure the construction of knowledge by levels, making them correspond to certain actions. The research methods used point to the use of documents of the specialty as a method of gathering information and the application of the systemic-structural approach, as well as the analytical-synthetic as methods that are used for the processing of the information collected, for the sake of Her organization. The main results obtained are configured in the classification of the objectives, the identification of the learning objectives and the system of actions, the execution of which is essential for obtaining and applying scientific knowledge.
Keywords: Learning; classification; knowledge; systemic approach; objective; teaching and learning objectives